Anti-angiogenic treatment promotes triple-negative breast cancer invasion via vasculogenic mimicry. Issue 4 (3rd April 2017) - Sun, Huizhi; Zhang, Danfang; Yao, Zhi; Lin, Xian; Liu, Jiameng; Gu, Qiang; Dong, Xueyi; Liu, Fang; Wang, Yi; Yao, Nan; Cheng, Siqi; Li, Linqi; et al.
ABSTRACT: Agents that target angiogenesis have shown limited efficacy for human triple-negative breast cancer (TNBC) in clinical trials. Along with endothelium-dependent vessels, there is also vasculogenic mimicry (VM) in the microcirculation of malignant tumors. The role of VM is not completely understood regarding anti-angiogenic treatment. In this study, human TNBC MDA-MB-231 and Hs578T and non-TNBC MCF-7 and BT474 tumor-bearing mice were treated with sunitinib, an anti-angiogenic drug, using a clinically relevant schedule. The drug was administered for one week and then discontinued. Tumor growth and invasion were observed, and the microcirculation patterns were detected with PAS/endomucin staining. Moreover, hypoxia and VM-associated proteins were evaluated with Hypoxyprobe kits and immunohistochemistry, respectively. Sunitinib significantly inhibited tumor growth in the TNBC and non-TNBC tumors. However, MDA-MB-231 and Hs578T tumors regrew and were more aggressive when the treatment was stopped. The discontinuation had no significant effect on the behavior of the non-TNBC MCF-7 and BT474 tumors. The growth of endothelium-dependent vessels in the TNBC MDA-MB-231 and Hs578T tumors were blocked by sunitinib, during which the number of VM channels significantly increased and resulted in a rebound of endothelium-dependent vessels after sunitinib discontinuation. Moreover, the VM-associated proteins VE-cadherin and Twist1 upregulated in the sunitinib-treated MDA-MB-231 and Hs578T tumors. Furthermore, the clinical significance of this upregulation was validated in 174 human breast cancers. The results from human breast cancer specimens indicated that there were more VM-positive TNBC cases than those in non-TNBC cases. HIF-1α, MMP2, VE-cadherin, and Twist1 were also expressed in a higher level in human TNBC compared with non-TNBC. In aconclusion, sunitinib promoted TNBC invasion by VM. The VM status could be helpful to predict the efficacy of anti-angiogenic therapy in patients with TNBC.